Biological activity of non-radical vs. stable radical of a pyridazine-sulfonamide aminophenol-type compound. (7th September 2022) - Chatterjee, Himadri Sekhar; Maity, Suvendu; Halder, Satyajit; Ghosh, Prasanta; Jana, Kuladip; Mahapatra, Pradip Kumar; Sinha, Chittaranjan
Abstract : A redox-non-innocent 2-aminophenolate derivative 4-(3, 5-di- tert -butyl-2-hydroxyphenylamino)- N -(6-methoxypyridazin-3-yl)benzenesulfonamide (LSOAP H2 ) is more activity against cancer cell lines than one electron-oxidized form o -iminosemiquinonate monoanion (LSOISQ ). Abstract : 4-(3, 5-Di- tert -butyl-2-hydroxyphenylamino)- N -(6-methoxypyridazin-3-yl)benzenesulfonamide (LSOAP H2 ) is an 2-aminophenol-appended, redox-non-innocent molecule. It was characterized structurally by spectroscopy and its structure was confirmed by single-crystal X-ray diffraction. The o -iminosemiquinonate monoanion (LSOISQ ) was obtained by one electron-oxidation and confirmed by electron paramagnetic resonance (EPR) spectroscopy and UV-vis spectroscopy. Cyclic voltammetry showed two consecutive redox couples: o -amidophenolate/ o -iminosemiquinonate monoanion (LSOAP H2 /LSOISQ ) and o -iminosemiquinonate monoanion/ o -benoquinone (LSOISQ /LSOIQ ). The radical features of LSOISQ in air were supported by EPR spectroscopy ( g = 2.005) in a solution at room temperature. Computation based on density functional theory revealed the spin density to be localized on LSOISQ due to formation of the o -iminosemiquinonatemonoanion radical. The in vitro toxicity of LSOAP H2 and LSOISQ was estimated against human cancer cell lines (HepG2, MDA-MB 231, HeLa) and a human normal cell line (WI-38). The cellular metabolic activity of LSOAP H2 and LSOISQ were determined using the MTT assay using the cell lines stated above. LSOAP H2 and LSOISQ enhanced cellular levels of reactive oxygen species in human cancer cell lines, which culminated in the inactivation/death of cancer cells. LSOISQ was more effective than LSOAP H2 as an anticancer agent.